Ice algal communities in the Chukchi and Beaufort Seas in spring and early summer: Composition, distribution, and coupling with phytoplankton assemblages. (20th December 2017) - Selz, Virginia; Laney, Samuel; Arnsten, Alexandra E.; Lewis, Kate M.; Lowry, Kate E.; Joy‐Warren, Hannah L.; Mills, Matthew M.; van Dijken, Gert L.; Arrigo, Kevin R.
Abstract: To understand the controls on distributions of ice algal communities in spring and the role of ice algae in under‐ice bloom development through possible seeding, we sampled the ice and water column in the Chukchi and Beaufort Seas over spring and summer. Field observations showed that high springtime concentrations of bottom ice algal communities were released from the ice into the water column by summer. Furthermore, during our spring sampling, bottom ice algal concentrations were highly variable. Declines in spring ice algal biomass and physiological state were correlated with ice melt, rather than light or nutrient availability. Nonparametric multivariate data analysis of the seasonal succession of phytoplankton and ice algal community composition illustrated that the loss of algae from the sea ice temporarily elevated water column chlorophyll a (Chl a ) levels, as ice‐derived taxa dominated the phytoplankton biomass. Model simulations, constrained by field observations from this study, further suggested that seeding by ice algae was brief and alone could not account for the phytoplankton biomass concentrations exceeding 2 mg Chl a m −3 observed in our study. Ice algal sloughing from the sea ice to the water column contributes biomass to the phytoplankton community. However, this signal of ice‐derived taxa is brief and non‐ice derived taxa dominate phytoplankton blooms later in the spring and summer.